(untitled) (Research, Society and Development, 2021)
Objective: to report on how we carry out the cleaning process of flexible endoscopes. Method: a descriptive study, experience report type, about the cleaning and disinfection process of flexible endoscopes in a teaching hospital in southern Brazil. Results: after using the flexible endoscope, start the leak test in the examination room right after the end of the procedure, together with a pre-cleaning of the device in a vat of diluted enzymatic detergent solution. Visual inspection should be performed prior to performing high-level disinfection, according to its classification as a critical accessory, used in invasive procedures with penetration of the skin, mucous membranes, sterile spaces or cavities, sub-epithelial tissues and vascular system. After manual cleaning, the automated cleaning process is performed, including rinsing and high-level disinfection. Then the device is identified on the processing carried out and stored in cabinets in the vertical position. Conclusion: the reprocessing of flexible endoscopes must follow recommendations based on evidence in updated guidelines, investment in the physical structure with correct flows and storage of equipment in a manner appropriate to the reality of the service to reduce the rate of infection.